Cardiovascular Risk Assessment after Sofosbuvir and Daclatasvir Regimen for Chronic Hepatitis C Virus Infection - Kareem Ali Maher; Reda Biomy Bastawesy; Mahmoud Mohammed AbdouYossef; Mariam Salah Zaghlol; Wael Anwer Haseeb (Journal of the Pakistan Medical Association, 2023)
Objective: To assess cardiovascular risk after sofosbuvir and daclatasvir antiviral combination therapy in chronic hepatitis C virus patients. Methods: The prospective cohort study was conducted at the Kafrelsheikh University Hospital, Egypt, from December 2019 to December 2021, and comprised adult patients of either gender with chronic hepatitis C virus and with minimum ejection fraction 40%. They were classified into groups according to their cardiovascular risk. Group 1 had individuals with no risk factors, Group 2 had patients with many risk factors, Group 3 had patients with only hypertension, Group 4 had those with diabetes alone, and Group 5 comprised smokers. All the patients were evaluated for the risk of major cardiovascular events at baseline and at the end of 12-week of antiviral combination therapy of sofosbuvir 400 mg once daily dose and daclatasvir 60 mg once daily dose. Data was analysed with SPSS version 23. Results: Of the 200 patients, there were 96(48%) males and 104(52%) females. The age ranged 34-81 years. There were 78(39%) patients in Group 1; 20(25.6%) males and 58(74.4%) females with mean age 54.4±10.45 years. Group 2 had 60(30%) patients; 40(66.6%) males and 20(33.3%) females with mean age 59.57±9.1 years. Group 3 had 25(12.5%) patients; 3(12%) males and 22(88%) females with mean age 61.4±7.8 years. Group 4 had 13(6.5%) patients; 10(77%) males and 3(23%) females with mean age 55.4±10.4 years. Group 5 had 24(12%) patients who were all (100%) males with mean age 60.7±5.7 years. There were non-significant changes in the incidence of angina, arrhythmias or progression of dyspnoea (p>0.05). Echocardiography follow-up results showed non-significant changes in mean ejection fraction, global longitudinal strain and pulmonary artery pressure (p>0.05). Conclusion: Sofosbuvir and daclatasvir combination therapy was found to be safe in chronic hepatitis C virus patients regarding cardiac risks. Keywords: Sofosbuvir, Daclatasvir, Stroke, Pulmonary, coronary syndrome, Cardiovascular, Hepatitis C, Ventricular dysfunction, Echocardiography, Amiodarone, Hypertension, Arrhythmias, Diabetes, Dyspnoea, Smoking.